Tata Kelola Aksesibilitas Layanan Publik bagi Perempuan Penyandang Disabilitas di Perkotaan dalam Perspektif Komunitas Spooniestory - Alita Aura Zahir; Calista Mutiara Uma; Nabilah Nameera Ruzdi; Aniqotul Ummah; Chomariyana Kartika Hesti (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The realization of accessible public services is a crucial requirement for creating an inclusive urban environment for all, including women with disabilities. However, in practice, this group still faces various obstacles that limit their access to public services. This study aims to describe the accessibility of public services, identify various obstacles experienced by women with disabilities, and analyze the governance and implementation of accessibility policies from the perspective of the Spooniestory Community. The research was conducted using a qualitative approach through observation, interviews, documentation, and document studies. The results show that some public services have attempted to provide more disability-friendly facilities, but their implementation remains uneven and does not fully meet the needs of women with disabilities, particularly those with invisible disabilities. Obstacles identified include limited facilities, social stigma, gender-based discrimination, and services that do not fully understand user needs. These findings emphasize that accessibility is determined not only by the availability of physical facilities, but also by inclusive governance and the ability of public policies to accommodate the experiences of vulnerable groups.